2013
DOI: 10.1016/j.enggeo.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and engineering properties of Tiller clay

Abstract: A. Gylland et al. ABSTRACT 25A detailed characterisation of the quick clay underlying the NTNU research site at Tiller, 26 Trondheim is presented. The objective of the work is to provide guidance on quick clay 27 parameters to engineers and researchers working with similar clays in Scandinavia and 28North America especially on landslide hazard assessment. The material is lightly 29 overconsolidated and is characterised by its high degree of structure and very high 30 sensitivity (quick clay). Clay and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…Although the marine clays in southeast Norway have similar depositional history and mineralogy to those in the mid-Norway area, they often have slightly higher clay content and consequently higher water content and lower bulk unit weight. Most notably they are usually of higher plasticity (e.g., Gylland et al 2013). Long and Donohue (2007) previously presented data similar to that shown in Fig.…”
Section: Sites In Southeast Norwaysupporting
confidence: 72%
“…Although the marine clays in southeast Norway have similar depositional history and mineralogy to those in the mid-Norway area, they often have slightly higher clay content and consequently higher water content and lower bulk unit weight. Most notably they are usually of higher plasticity (e.g., Gylland et al 2013). Long and Donohue (2007) previously presented data similar to that shown in Fig.…”
Section: Sites In Southeast Norwaysupporting
confidence: 72%
“…However, due to the limitations of this study more investigations are needed before conclusions can be drawn. The theoretical value of the RES after the unloading of the sensitive Tiller clay is p′ ps = − u ps = 65 kPa, with an assumed K′ 0 = 0·5 (based on Brooker & Ireland, 1965;Gylland et al, 2013). The observed maximum RES ( p′ r = 13·7 kPa when the sample is above ground) is very low compared with a theoretical value of 65 kPa and p′ r /p′ ps = 0·21 and p′ r /σ′ v0 = 0·14.…”
Section: Resultsmentioning
confidence: 92%
“…(1997b) and Sandven (1990) literature (e.g. Sandven et al, 2004;Gylland et al, 2013;Amundsen et al, 2016b) and the geotechnical profile is shown in Fig. 2.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…In Norway, Gylland [13] stated that vane shear test has been used as in-situ test equipment since the past years. However, this method tends to be less popular because of CPTU-test.…”
Section: Vane Shear Testmentioning
confidence: 99%
“…The advantages of vane shear test are less timeconsuming, and it is applicable in homogeneous deposits [13]. The effect of different vane size is minor in most soil and by applying two different vanes with different length to a diameter ratio in the same stratum, the soil strength anisotropy can be inferred [21].…”
mentioning
confidence: 99%